Households' food expenditures in urban areas of Iran: An application of small area estimation (Epidemiology, Biostatistics, and Public Health, 2022)
Background: A fundamental factor for human development is food, and inequalities in nutrition have been related to inequalities in health .The purpose of this study was to estimate Household Food Expenditure (HFE) in urban areas of Iran at district-level using small area estimation (SAE) methods. Design and Methods: We used the Fay-Herriot model, the well-known area-level model of SAE. The main data was urban data of HFE collected by Statistical Centre of Iran at 2013. The environment of our study was urban area of Iran and study unit was household.Results: Findings showed that average number of room at each household, migration rate, proportion of male headed households(PMH) and Proportion of the active population`s employed at district level had a significant effect on HFE. Comparison between aggregated province estimates and estimates reported by SCI was not significant (P=0.609). The lowest and the highest HFE belong respectively to Pishva district with 27,067 thousand rials(TRs) and to Boyer-Ahmad district  with 85,175 TRs.Conclusions: Small-area estimation is advantageous for surveillance of HFE at the district level. This method allows documentation of geographic disparities and improves our understanding of the spatial distribution of HFE in urban areas of Iran.